2020
DOI: 10.1017/cjn.2020.96
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Neurologic Exam: Instructional Videos and Guidance for the COVID-19 Era

Abstract: ABSTRACT Objective: To outline features of the neurologic examination that can be performed virtually through telemedicine platforms (the virtual neurological examination [VNE]), and provide guidance for rapidly pivoting in-person clinical assessments to virtual visits during the COVID-19 pandemic and beyond. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 9 publications
0
41
0
12
Order By: Relevance
“…Our introductory course therefore focused on video communication skills, the virtual physical examination, documentation changes and technology troubleshooting to help build resident competency in this new framework. Many recent articles detail best practices for the virtual physical examination, 11 and the neurological 12 and musculoskeletal 13 14 examinations in particular. One study showed non-inferiority of the virtual shoulder examination compared with the traditional ‘in person’ examination.…”
Section: Discussionmentioning
confidence: 99%
“…Our introductory course therefore focused on video communication skills, the virtual physical examination, documentation changes and technology troubleshooting to help build resident competency in this new framework. Many recent articles detail best practices for the virtual physical examination, 11 and the neurological 12 and musculoskeletal 13 14 examinations in particular. One study showed non-inferiority of the virtual shoulder examination compared with the traditional ‘in person’ examination.…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth is an expanding field with increasing understanding of what is possible through this medium for both acute and chronic consultations [ 43 ]. There are now several publications that describe a virtual neurologic examination [ 44 , 45 ]. There is also a growing number of publications addressing the possibility of virtual spine examination [ 46 , 47 , 48 ], although none of these virtual examinations have been studied for validity or reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Access to an online video library of patient encounters mitigated the loss of direct patient contact (Mian and Khan, 2020). Others have used videos to demonstrate clinical examination techniques (Al Hussona et al, 2020). Students were directed to large online resources such as YouTube videos and podcasts.…”
Section: Remedial Measuresmentioning
confidence: 99%